Dual Role of a Ricinoleic Acid Derivative in the Aqueous Synthesis of Silver Nanoparticles. (23rd March 2017) - Costa, Isadora Dantas; Wanderley Neto, Alcides de Oliveira; da Silva, Heloiza Fernanda Oliveira; Moraes, Edgar Perin; Damascena Nóbrega, Eryka Thamyris; Sant'Anna, Celso; Eugenio, Mateus; Gasparotto, Luiz Henrique da Silva
Abstract : We show that sodium 9, 10-epoxy-12-hydroxytetradecanoate (SEAR), an epoxidized derivative of ricinoleic acid, simultaneously functioned as reducing and stabilizing agents in the synthesis of silver nanoparticles in alkaline aqueous medium. The advantage of using SEAR is its biodegradability and nontoxicity, which are important characteristics for mitigation of environmental impact upon discharge of nanoparticles into terrestrial and aquatic ecosystems. The SEAR concentration was found to impact considerably the size distribution of silver nanoparticles (AgNPs). A concentration below the SEAR critical micelle concentration (CMC) generated 23 nm sized AgNPs with 10 nm standard deviation, while 50 nm sized AgNPs (σ = 21  nm) were obtained at a concentration above the SEAR CMC. FTIR analysis revealed that the carboxylate that constitutes the SEAR hydrophilic head binds directly to the AgNPs surface promoting stabilization in solution. Finally, AgNPs turned into Ag2 S upon contact with wastewater samples from Wastewater Treatment Plant at Federal University of Rio Grande do Norte (UFRN), Brazil, which is an interesting result, since Ag2 S is more environmentally friendly than pure AgNPs.